Sanctuary schematics and temple ideology in the Hebrew Bible and Dead Sea Scrolls: The import of Numbers - Spoelstra, Joshua J. (2022)
The temple schematics in the Dead Sea Scrolls (DSS), that is, New Jerusalem and Temple Scroll, has often been comparatively examined with the sanctuary structures in the Hebrew Bible (HB) (Ezk 40–48 and Num 2). Typically, in scholarship, the irreconcilable differences between all accounts (regarding the size, shape, name-gate ordering, etc.) is underscored, thus rendering a literary conundrum. This article argues that New Jerusalem and Temple Scroll drew from both Ezekiel 40–48 and Numbers 2 in different ways, purporting the sect(s)’s theologies and ideologies which accords, further, with the life setting of the Qumran communities; the influence of Numbers in the DSS is underscored. These aspects include (1) the eastern orientation of sacred structures and the compound at Khirbet Qumran, (2) the precise locale of the communities at the Dead Sea vis-à-vis Ezekiel 47 and (3) the desert encampment configuration together with its militaristic overtones in Numbers, which corresponds to the DSS sect(s)’s apocalyptic expectations as indicated in the War Scroll. Consequently, the Qumran sect(s) truly saw itself as an alternative priesthood of the forthcoming restored temple of God, even as in the interim they functioned as an alternative sanctuary (4QFlor; 4QMMT; 1QS). The import of Numbers upon the DSS sect(s)’s temple ideologies and priestly theologies is, therefore, equivalent to that of Ezekiel.Contribution: This article traces theological themes of temple and priestly ideologies between and among the Qumran literature and Hebrew Scriptures; both the respective library or canon and methodological approach are core to the historical thought’s aim and scope of HTS Teologiese Studies/Theological Studies.
Keywords: Ideology; Theology; Temple; Wilderness Sanctuary; Numbers 2; Ezekiel 40–48; Temple Scroll; New Jerusalem